2013
DOI: 10.1080/09205063.2013.766784
|View full text |Cite
|
Sign up to set email alerts
|

An innovative quaternary ammonium methacrylate polymer can provide improved antimicrobial properties for a dental adhesive system

Abstract: A quaternary ammonium methacrylate polymer (QAMP) with antimicrobial potential was synthesized. The resulting product (QAMP) was characterized by FTIR spectroscopy, NMR spectroscopy, visible spectrophotometry, XRPD and TGA. The in vitro susceptibility tests against Streptococcus mutans of QAMP were investigated prior and after incorporation into a commercial adhesive system (Clearfil™ SE Bond). The release of quaternary ammonium compounds from the experimental adhesive system (Clearfil™ SE Bond + 5% QAMP) was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 27 publications
0
28
0
Order By: Relevance
“…Generally speaking, however, with the increase of the amount of antibacterial agent, the mechanical properties and biocompatibility of the material will decrease. QACs belong to a kind of nonrelease antibacterial agent, and the antibacterial effect can be achieved when the dosage is relatively large 32,[44][45][46][47] . While the release antimicrobial agents can achieve better antibacterial effect at a low concentration, however, their extending antibacterial efficiency is low and they may be more toxic toward surrounding environments, the so-called "sudden release effect" [104][105][106][107] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Generally speaking, however, with the increase of the amount of antibacterial agent, the mechanical properties and biocompatibility of the material will decrease. QACs belong to a kind of nonrelease antibacterial agent, and the antibacterial effect can be achieved when the dosage is relatively large 32,[44][45][46][47] . While the release antimicrobial agents can achieve better antibacterial effect at a low concentration, however, their extending antibacterial efficiency is low and they may be more toxic toward surrounding environments, the so-called "sudden release effect" [104][105][106][107] .…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, 5 wt% DMADDM was incorporated into Clearfil SE Bond by Zhang et al It had been observed that adhesives containing DMADDM inhibited the growth, lactic acid production, and Exopolysaccharides (EPS) metabolism of S. mutans biofilm at different stages, with no adverse effect on its dentin adhesive bond strength 44,45) . Besides that, Pupo et al 46,47) performed a study incorporating of quaternary ammonium methacrylate polymer (QAMP) at 5% by mass to Clearfil SE Bond as experimental group, Clearfil SE Bond as negative control group, and Clearfil Protect Bond as positive control group. The results showed that experimental group demonstrated the minimum inhibitory /bactericidal concentration (MIC/MBC) values and an inhibition zone against Lactobacillus casei (L. casei) and Actinomyces naeslundii (A. naeslundii) similar to the positive control, and higher MIC/MBC values and smaller inhibition zone than the negative control for S. mutans, L. casei, and A. naeslundii, and that no statistically significant difference in the resin-dentin bond strength (μTBS) was observed between experimental and negative control groups immediately, after 6 months, or 12 months of water storage.…”
Section: Adhesive Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…This innovative product was then incorporated into self-etching adhesive systems and provided an enhanced antibacterial effect against Streptococcus mutans. 6 In addition, QAMP avoided the rapid release of quaternary ammonium molecules from the dental adhesive system in contrast to that observed for the commercial product containing MDPB due to its polymeric structure. 6 Despite great progress concerning new dental polymers, their use as dental products is still controversial due to some toxic effect on the cells of pulpo-dentine complex.…”
Section: Introductionmentioning
confidence: 98%
“…6 In addition, QAMP avoided the rapid release of quaternary ammonium molecules from the dental adhesive system in contrast to that observed for the commercial product containing MDPB due to its polymeric structure. 6 Despite great progress concerning new dental polymers, their use as dental products is still controversial due to some toxic effect on the cells of pulpo-dentine complex. In that sense, quaternary ammonium compounds can show cytotoxicity to human pulpal cells, which requires their use in low concentration to ensure clinical safety.…”
Section: Introductionmentioning
confidence: 98%